Analisis Framing Model Robert Entman Kasus Pengembang Meikarta Gugat Konsumen pada Media Online Detik.Com dan Kompas.Com - Wahyu, Fachri Alfian; Nayiroh, Luluatu; Kusumaningrum, Rastri (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research was conducted based on the news about Meikarta developers suing Meikarta Consumers who are members of the Meikarta Consumer Care Community Association (PKPKM) for 56 billion rupiah on online media Detik.com and kompas.com using the Robert n Entman model framing analysis. The Robert n Entman framing model uses four elements that explain this research, including 1) Define Problem, 2) Diagnoses Causes 3) Make Moral Judgement 4) Treatment Recommendation. This research uses a qualitative approach method with descriptive nature. Based on the results of the analysis of the two online media using the Robert N Entman model, it was found that there was a difference in point of view between Detik.com and kompas.com. Differences in views on each media occur because each media has its own way of packaging in determining views in seeing and framing an event or issue that will be presented as news. The views made by each media can determine how a media frames and forms public opinion in society. Keywords : framing analysis, online media, meikarta